Enhancing Water Productivity in Agriculture at Fokshingkot Lift Irrigation System - Rajouria, Dinesh; Aryal, Padma Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Ranibas village of Foksingkot Village Development Committee (VDC), Palpa District, Nepal is a severe water scarce area. The nearest water source is spring water about 2.5 hours walk downhill (to and fro) to fetch a vessel of water and it is three hours for the farthest household of the area. A lift pumping system consisting of three stages, each of 100m lift and the fourth of 30m lift was (with total lifting of 330m), was constructed to deliver 1.94 liters per sec (l/sec) water for drinking purpose as well as for irrigation of five hectare of land. Despite failures of several lift pumping schemes for irrigation in Nepal, this high head lifting/pumping system has been successful. The 102 households are benefitted with easy availability of drinking water and also for irrigation with drip and sprinkler systems. The lift water supply system has helped in saving time of children and women for fetching water and also increased household income by farming supported by irrigation. The virtual labor saving value of one year surpasses the investment of the project. DOI: http://dx.doi.org/10.3126/hn.v10i0.7100 Hydro Nepal Vol.10 January 2012 32-35